Not enough : human rights in an unequal world - Moyn, Samuel (Cambridge, Massachusetts : Belknap Press of Harvard University Press, 2018)
"The age of human rights has been kindest to the rich. As state violations of political rights have garnered unprecedented attention in recent decades, a commitment to material equality has quietly disappeared. In its place, economic liberalization has emerged as the dominant economic force. In this provocative book, Samuel Moyn considers how and why we chose to make human rights our highest ideals while simultaneously neglecting the demands of a broader social and economic justice. Moyn places the human rights movement in relation to this disturbing shift and explores why the rise of human rights has occurred alongside exploding inequality"--Page 4 of cover
Jacobin legacy: the origins of social justice -- National welfare and the universal declaration -- FDR's second bill -- Globalizing welfare after empire -- Basic needs and human rights -- Global ethics from equality to subsistence -- Human rights in the neoliberal maelstrom.
Includes bibliographical references (pages 223-264) and index.
Keywords: Human rights -- History; Equality -- History; Welfare economics -- History; Neoliberalism -- History; Equality; Human rights; Neoliberalism; Welfare economics; History